First insight into lignin valorization as a promising biopolymer for the modulation of the physicochemical properties of Port wine - Pereira, Ana Rita (2024)
Lignosulfonate (LS), kraft lignin (KL), and organosolv lignin (OL) were evaluated as potential modulating agents of the physicochemical properties of Port wine at two different concentrations for 7 and 30 days. KL and LS demonstrated the ability to remove proteins and potentiate the anthocyanin concentration. LS reduced the tannin content and the interaction of salivary acidic proline-rich proteins with wine phenolic compounds. None of the lignin promoted a perceptible color change; however, the yellowish color of KL and OL at 100 g/hL contributed to an increase in the yellow tones of wines. Lignin improved wine aroma by reducing the amount of unwanted volatiles by 30% and increasing the content of ethyl esters associated with fruity aromas by up to 60%. The results suggest that lignin, especially LS, can be employed as a modulating agent, positively impacting wines physicochemical properties. This valorization of a byproduct opens up new opportunities for the wine industry.